13th International Conference on Theory and Application of Fuzzy Systems and Soft Computing - ICAFS-2018 - Aliev, Rafik A.; Kacprzyk, Janusz; Pedrycz, Witold; Jamshidi, Mo.; Sadikoglu, Fahreddin M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the proceedings of the 13th International Conference on Application of Fuzzy Systems and Soft Computing (ICAFS 2018), held in Warsaw, Poland on August 27-28, 2018. It includes contributions from diverse areas of soft computing such as uncertain computation, Z-information processing, neuro-fuzzy approaches, evolutionary computing and others. The topics of the papers include theory of uncertainty computation; theory and application of soft computing; decision theory with imperfect information; neuro-fuzzy technology; image processing with soft computing; intelligent control; machine learning; fuzzy logic in data analytics and data mining; evolutionary computing; chaotic systems; soft computing in business, economics and finance; fuzzy logic and soft computing in the earth sciences; fuzzy logic and soft computing in engineering; soft computing in medicine, biomedical engineering and the pharmaceutical sciences; and probabilistic and statistical reasoning in the social and educational sciences. The book covers new ideas from theoretical and practical perspectives in economics, business, industry, education, medicine, the earth sciences and other fields. In addition to promoting the development and application of soft computing methods in various real-life fields, it offers a useful guide for academics, practitioners, and graduates in fuzzy logic and soft computing fields.
From status quo bias to innovative multiagent decisions under fuzzy preferences and fuzzy majority -- Bimodal information clustering methods -- Maximum likelihood estimation from interval-valued data. Application to fuzzy clustering -- Theory and practice of material development under imperfect information -- Forming and Quantifying Consensus in Distributed System Modeling and Group Decision-Making:A Perspective of Granular Computing -- Why multidimensional fuzzy arithmetic? -- On Using Fuzzy Sets in Healthcare Process Analysis -- Optimization of Jobs in GIS by Coloring of Fuzzy Temporal Graph -- Algebraic Properties Of Z -Numbers Under Multiplicative Arithmetic Operations -- Z-number based TOPSIS method in multi-criteria decision making -- Comparative Analysis of Artificial Intelligence Based Methods for Prediction of Precipitation. Case Study: North Cyprus -- Analysis and Processing of Informationin Economic Problems. Crisp and Fuzzy Technologies -- Labeled Fuzzy Rough Sets in Multiple-criteria Decision-making -- Comparing Image Distortion of LSB -- An Effective Fuzzy Controlled Filter for Feature Extraction Method -- Analysis of Prediction Models for Wind Power Density, Case Study: Ercan Area, Northern Cyprus -- Evaluation of Image Representations for Player Detection in Field Sports using Convolutional Neural Networks -- A Fuzzy Based Gaussian Weighted Moving Windowing for Denoising Electrocardiogram (ECG) Signals -- Integrated Deep Learning Structures For Hand Gesture Recognition -- Rule Based Intelligent Diabetes Diagnosis System -- Intensive Investigation in Differential Diagnosis of Erythemato-Squamous Diseases -- A Computational-Intelligence Based Approach to Diagnosis of Diabetes Mellitus Disease -- Fuzzy Expert system for rectal cancer.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence